Production and Optimization of α-Amylase from Aspergillus flavus under Solid State Fermentation (Indo-American Journal of Life Sciences and Biotechnology, 2022)
An important and well-known industrial enzyme that breaks down starch or glycogen is alpha amylase. It iscost-effective to use microorganisms to produce amylase because they may be easily engineered to produceenzymes with specific properties. The filamentous structure of fungi makes them an ideal alternative tobacteria in enzyme synthesis. The synthesis of enzymes might benefit greatly from agricultural wastebyproducts. The amylase production by Aspergillus flavus was carried out by solid state fermentation usingtwo naturally occurring carbon sources, namely rice bran and wheat bran. The enzyme activity that wasobtained was lowest from rice bran (428 ± 24μmol./min/mL) and greatest from wheat bran (670 ±36μmol./min/mL). At a temperature of 30°C, with an optimal inoculum size of 10% (660 ± 36μmol./min./mL),an incubation duration of 120 hours (670 ± 28 μmol./min./mL), and a pH of 6 (680 ± 42μmol./min./mL), themaximum yield of enzyme synthesis was achieved. By adding 0.2 percent MgSO4 and 0.022 percent CaCl2,the amylase production yield was maximized. Based on the findings of this investigation, Aspergillus flavusmight be a good candidate for using in industrial α-amylase production.